Overcoming the Challenges of Poor Architectural Planning in Nigerian Performance Spaces: The Outstanding Legacies of Duro Oni - Iwuh, John (Centre for Black and African Arts and Civilization (CBAAC), 2012)
Ideal theatre structures in Nigeria are few. Consequently, the phrase performance spaces' best describes the majority of the stages where drama is performed, whether in our academic institutions or other spaces originally built for multipurpose uses. A number of theatre halls, including 'arts theatres' in institutions of higher learning in Nigeria, fall into this category. This trend, whether consciously or unconsciously, is a neglect of the professional environment required for theatre practice. Ignorance of what the practice entails is only one reason among the many that account for these shortcomings. In this regard, the contributions of Duro Oni towards correcting some of these anomalies and raising them to acceptable standards for events or theatre performances underscores the need to involve professional theatre designers in theatre planning. The uncompromising insistence on basic standards in his project has become not only crucial departures from existing norms but also milestones in indigenous theatre consulting. This article addresses the need fora policy that can mandate the body of architects and builders to embrace academic "theatre consultants" with a track record of professional practice, pending the time a body of chartered theatre consultants will be registered in Nigeria.
Keywords: Architectural planning; Performance spaces; Lighting design; Theatre consultancy